Simultaneous detection of Listeria monocytogenes and pathogenic Vibrio by dual peptide nucleic acid fluorescence in situ hybridization - WU Shan; LI Ke; FANG Yun; LOU Chengjie; YU Huizhen; ZHANG Mingzhe; SHUAI Jiangbing; ZHANG Xiaofeng (浙江大学学报. 农业与生命科学版, 2018)
Listeria monocytogenes and pathogenic Vibrio are common and harmful foodborne pathogens in daily life. Besides the culture-based, biochemical, immunological and molecular methods for applications in clinical diagnostics and food microbiology, fluorescence in situ hybridization (FISH) using labeled peptide nucleic acid (PNA) probes as an alternative methodology for detection of L. monocytogenes and Vibrio were developed. To improve the efficiency, multi-probe PNA-FISH assay was established for simultaneous detection of multiple microorganisms. Based on the singlet PNA probe for detection of L. monocytogenes and Vibrio, respectively, by labeling different fluorescent dyes to the specific PNA probes, the PNA-FISH procedure for simultaneous detection of L. monocytogenes and Vibrio was optimized. By the usage of a Leica DM 6000B fluorescence microscope, four kinds of fluorescence filter cubes I3, L5, N21 and Y3 were compared after labeled with FAM and Cy3 fluorescences. As a result, for dual fluorescence detection, the combination of L5 and Y3 was suggested to observe the green fluorescence and red fluorescence, respectively. Comparing the effect of the volume ratio of the two strain solution on the test results, when the ratio decreased from 1∶1 to 1∶9, both strains could be detected; when the ratio decreased to 1∶19, the less was difficult to observe. It is indicated that, after labeled with FAM and Cy3 fluorescences, green and red fluorescences released by PNA probes can be observed through filter cubes L5 and Y3, respectively, within the usage of Leica DM 6000B fluorescence microscope, suggesting that the PNA-FISH synchronously detecting dual-species bacteria can be achieved by ordinary fluorescence microscope, if choosing suitable fluorescent dyes and fluorescence filter cubes.